2003
DOI: 10.3168/jds.s0022-0302(03)73790-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GnRH Administered to Cows at the Onset of Estrus on Timing of Ovulation, Endocrine Responses, and Conception

Abstract: Two experiments examined effects of GnRH administered within 3 h after onset of estrus (OE) on ovulation and conception in dairy cows. In experiment 1, 46 cows received either saline, 250 microg of GnRH, or 10 microg of the GnRH analogue, Buserelin. Cows were observed for estrus, blood samples were collected, and ovulations were monitored by ultrasound. In controls, 76% of cows had intervals from estrus to ovulation of < or = 30 h and 24% had intervals > 30 h. Treatment with either GnRH or GnRH analogue (data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
63
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 35 publications
7
63
4
2
Order By: Relevance
“…In several previous studies, GnRH improved pregnancy rate by 7-21% in lactating dairy cows (Lee et al, 1983;Nakao et al, 1983;Stevenson et al, 1990;Kaim et al, 2003;Lopez-Gatius et al, 2006). On the other hand, in some studies the pregnancy rate was not affected by GnRH treatment follow- ing AI and was similar to our findings (Stevenson et al, 1984;Lee et al, 1985;Chenault 1990;Mee et al, 1990;Perry and Perry 2009).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In several previous studies, GnRH improved pregnancy rate by 7-21% in lactating dairy cows (Lee et al, 1983;Nakao et al, 1983;Stevenson et al, 1990;Kaim et al, 2003;Lopez-Gatius et al, 2006). On the other hand, in some studies the pregnancy rate was not affected by GnRH treatment follow- ing AI and was similar to our findings (Stevenson et al, 1984;Lee et al, 1985;Chenault 1990;Mee et al, 1990;Perry and Perry 2009).…”
Section: Discussionsupporting
confidence: 81%
“…However, the administration of GnRH at the time of AI, approximately 12 h after the initiation of standing oestrus, need not result in a greater surge of LH (Lee et al, 1985;Lucy and Stevenson 1986;Mee et al, 1990). In addition, the insufficient LH surge did not have any ovulatory effect (Lee et al, 1985;Lucy and Stevenson, 1986;Kaim et al, 2003) and did not improve pregnancy (Lee et al, 1985). Thus our result and previous studies indicated that the administration of GnRH at the time of AI did not affect pregnancy rate.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations